At least two mutant alleles of ornithine delta-aminotransferase cause gyrate atrophy of the choroid and retina in Finns. - Mitchell, G A (1989)
Gyrate atrophy of the choroid and retina (GA) is an inherited chorioretinal degeneration caused by deficiency of ornithine delta-aminotransferase (OAT; L-ornithine: 2-oxo-acid aminotransferase; EC 2.6.1.13). GA is one of the "Finnish genetic diseases," a group of several rare monogenic disorders that occur with increased frequency in the Finnish population. Using a combination of RNase A protection, genomic cloning, and polymerase chain reaction amplification of genomic DNA, we found one of two missense mutant OAT alleles to be present in each of 16 Finnish GA pedigrees. The first mutation R180T, in which arginine-180 is replaced by threonine, was present in homozygous form in patients from two pedigrees. The second mutation L402P, in which leucine-402 is replaced by proline, was present in homozygous form in patients from 14 pedigrees. Neither mutation was present in 19 Finnish controls. L402P was not present in 18 non-Finnish GA patients but R180T was found in an American GA patient. We constructed full-length mutant cDNAs by amplifying patient cDNA with the polymerase chain reaction and cloning a restriction fragment containing the mutation into an otherwise normal human OAT cDNA. These mutant cDNAs were then expressed in CHO-K1 cells, which lack endogenous OAT. Both R180T and L402P inactivate OAT. These results show molecular heterogeneity in GA alleles even in the Finnish population.